Exploring Neologisms in Youth Press: In the Example of Uzbek and English Languages (Journal of Pedagogical Inventions and Practices, 2024)
This study explores the phenomenon of neologisms in the youth press, focusing on examples from both Uzbek and English languages. Through a corpus-based analysis, we investigate the emergence, semantic characteristics, and sociolinguistic implications of these linguistic innovations. Our findings highlight the dynamic nature of youth language and its reflection of cultural trends and identity construction